Numerical investigation of a hybrid serpentine-pin flow field for enhanced PEMFC performance under variable operating conditions - Sevinc, Huseyin (Elsevier - Division Reed Elsevier India Pvt Ltd, 2026)
This study introduces a novel hybrid flow field configuration, termed ser-pin, developed to enhance the performance of proton exchange membrane fuel cells (PEMFCs) by integrating serpentine and pin-type geometries. The proposed design was numerically investigated using a single-cell PEMFC model through CFD simulations in ANSYS Fluent. A widely adopted triple-serpentine configuration was used as a benchmark to evaluate the electrochemical and fluidic performance of the hybrid structure. Comparative analyses were conducted under seven operating scenarios that included variations in cell temperature (50-70 degrees C), relative humidity (25-100%), and pressure (1-2 atm). Key performance parameters such as current density, power density, reactant and water distributions, temperature profiles, pressure drop, and reaction heat source behavior were comprehensively examined. The results consistently demonstrated that the ser-pin design outperformed the conventional layout in all tested conditions. At 0.3 V, the hybrid configuration achieved peak current densities of up to 1.27 A/cm2, while the maximum power density of 0.49 W/cm2 was attained at 0.5 V, indicating improvements of approximately 6-8% over the reference design. The pin-type region significantly contributed to better reactant mixing, thermal homogeneity, and reduced local flooding or dehydration. Despite a higher pressure drop due to added geometric complexity, the overall performance gain proved substantial. These findings suggest that hybrid architectures with spatially functional features can address the limitations of traditional single-pattern designs and offer promising potential for next-generation PEMFC systems.
Keywords: PEM fuel cell; Hybrid flow field; Numerical simulation; Reactant distribution; Power density improvement